Attenuated initial serum ferritin concentration in critically ill coronavirus disease 2019 geriatric patients with comorbid psychiatric conditions - Abulseoud, Osama A.; Yehia, Asmaa; Egol, Claudine J.; Nettey, Victor N.; Aly, Mohamed; Qu, Yihuai; Skolnik, Aaron B.; Grill, Marie F.; Sen, Ayan; Schneekloth, Terry D. (Frontiers in Psychiatry, 2022)
We examined the effects of psychiatric comorbidity, sex, and ICU admission on serum ferritin concentration in 628 elderly patients (79.7 ± 8.5 years) with positive SARS-CoV-2 PCR test. Hospitalization was required in 96% of patients and 17% required ICU admission. Patients with COVID-19 and psychiatric comorbidities (n = 212) compared to patients without psychiatric comorbidities (n = 416) had significantly lower ferritin concentration (570.4 ± 900.1 vs. 744.1 ± 965, P = 0.029), a greater incidence of delirium (22.6 vs. 14.4%, P = 0.013) and higher mortality (35.3 vs. 27.6%, P = 0.015). Furthermore, we found significant effects for sex (P = 0.002) and ICU admission (P = 0.007). Among patients without comorbid psychiatric conditions, males had significantly higher ferritin compared to females (1,098.3 ± 78.4 vs. 651.5 ± 94.4, P < 0.001). ICU patients without comorbid psychiatric conditions had significantly higher serum ferritin compared to ICU patients with comorbid psychiatric conditions: (1,126.6 ± 110.7 vs. 668.6 ± 156.5, P < 0.001). Our results suggest that the presence of comorbid psychiatric conditions in elderly patients with COVID-19 is associated with higher rates of delirium and mortality and lower ferritin levels during severe illness. Whether high serum ferritin is protective during severe infection requires further investigation.